Is the effect of tinnitus on auditory steady-state response amplitude mediated by attention? - Diesch, Eugen; Andermann, Martin; Rupp, André (Frontiers in Systems Neuroscience, 2012)
Objectives: Auditory steady-state response (ASSR) amplitude enhancement effects have been reported in tinnitus patients. As ASSR amplitude is also enhanced by attention, the effect of tinnitus on ASSR amplitude could be interpreted as an effect of attention mediated by tinnitus. As N1 attention effects are significantly larger than those on the ASSR, if the effect of tinnitus on ASSR amplitude were due to attention, there should be similar amplitude enhancement effects in tinnitus for the N1 component of the auditory-evoked response. Methods: MEG recordings which were previously examined for the ASSR (Diesch et al., 2010a) were analyzed with respect to the N1m component. Like the ASSR previously, the N1m was analyzed in the source domain (source space projection). Stimuli were amplitude-modulated (AM) tones with one of three carrier frequencies matching the tinnitus frequency or a surrogate frequency 1½ octave above the audiometric edge frequency in controls, the audiometric edge frequency, and a frequency below the audiometric edge. Single AM-tones were presented in a single condition and superpositions of three AM-tones differing in carrier and modulation frequency in a composite condition. Results: In the earlier ASSR study (Diesch et al., 2010a), the ASSR amplitude in tinnitus patients, but not in controls, was significantly larger in the (surrogate) tinnitus condition than in the edge condition. Patients showed less evidence than controls of reciprocal inhibition of component ASSR responses in the composite condition. In the present study, N1m amplitudes elicited by stimuli located at the audiometric edge and at the (surrogate) tinnitus frequency were smaller than N1m amplitudes elicited by sub-edge tones both in patients and controls. The relationship of the N1m response in the composite condition to the N1m response in the single condition indicated that reciprocal inhibition among component N1m responses was reduced in patients compared against controls. Conclusions: In the present study, no evidence was found for an N1-amplitude enhancement effect in tinnitus. Compared to controls, reciprocal inhibition is reduced in tinnitus patients. Thus, as there is no effect on N1m that could potentially be attributed to attention, it seems unlikely that the enhancement effect of tinnitus on ASSR amplitude could be accounted for in terms of attention induced by tinnitus.